Mechanically stable, and reversible integration of microchips on textile: liquid metal-based anisotropic conductive adhesive - Sang Gil Lee; Kyeong-Bin Kim; Hyesu Choi; Joo Hwan Shin; Chanho Jeong; Geonoh Choe; Gyan Raj Koirala; Jae-seung Shim; Yujin Mun; Young Gil Kim; Yei Hwan Jung; Eun-Ho Lee; et al. (npj Flexible Electronics)
Abstract Integrating surface-mounted devices (SMDs) onto textiles remains a key challenge in wearable electronics due to textile surface irregularities and heat sensitivity. Conventional methods like soldering or anisotropic conductive films (ACFs) often fail in such environments. We introduce a low-stress anisotropic conductive adhesive (LS-ACA) composed of eutectic gallium–indium (EGaIn) liquid metal particles (LMPs) embedded in a pressure-sensitive SIS matrix. LS-ACA offers excellent electrical conductivity, mechanical flexibility, and durability under bending, stretching, and crumpling. Finite element analysis shows it reduces interfacial stress concentrations compared to soldering, maintaining uniform stress even under 10% strain. It achieves ultra-low contact resistance (1.5 mΩ at >64 wt% LMPs) and enables low-temperature bonding on diverse substrates. Moreover, LS-ACA supports over 10 reuse cycles without surface damage or performance loss. This scalable, reusable material offers a promising path for integrating electronics into fabrics, advancing sustainable and flexible wearable technologies.